Indonesian Women in Politics: Critical Analysis of Portrayal in Online News Sites - Susilo, Daniel; Sugihartati, Rahma; Arimbi, Diah Ariani (Jurnal ILMU KOMUNIKASI, 2019)
In 2004 Election, Indonesian government launched a policy mandatory 30 percent female representatives in the legislature. This is an effort to accelerate an increase of women’s representativeness in the parliament. This research describes the imaging of women as politicians in Indonesian online news sites: detikcom, Kompas.com, and Tribunnews.com. Van Dijk’s critical discourse analysis was utilized as method of this research with feminist critical analysis as the corresponding method. The result shows that the imaging of female politicians is in the domestic area. They are pictured as emotional and weak persons.